Debating Motherhood in Clément Vautel's Madame ne veut pas d’enfant (1924) - Christiansen, Hope (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2024)
Virtually neglected by literary scholars thus far, Clément Vautel’s Madame ne veut pas d’enfant (1924) is part of a subgroup of Belle Époque novels, including Jane de La Vaudère’s Les Demi-Sexes (1897), exploring the controversial subject of women’s reproductive freedom. The bulk of the Vautel’s characters fall into one of two groups: those who embrace the slogan “Croissez et multipliez” in the name of repopulating France and those who support a woman’s right to make her own decisions about having children. These debates replicate the real-life ones going on between pro-natalists and neo-Malthusians, the latter led by Paul Robin, whose Ligue pour la régénération humaine hosted lectures on birth control, sold contraceptives, distributed brochures, and supported abortion rights. The fact that Motherhood has become a significant topic of scholarly inquiry over the past decade and a half is all the more reason to investigate what Vautel has to say.